Spatiotemporal prioritization of soil erosion risk using the RUSLE model and CMIP6 projections under future climate scenarios in a Mediterranean watershed - İpek, Ahmet Faruk; Kahya, Ercan (Frontiers in Environmental Science, 2026)
Projected shifts in the Eastern Mediterranean rainfall regime suggest fewer but more intense precipitation events, which are expected to alter soil erosion dynamics. This study evaluates the spatiotemporal variations in rainfall erosivity (R-factor) and soil loss in the Küçük Menderes River Basin, Turkey, using the Geographic Information System (GIS) based Revised Universal Soil Loss Equation (RUSLE). The most appropriate R-factor formula was selected through a comparative evaluation of ten empirical approaches. Projections were based on downscaled rainfall data from 13 General Circulation Models (GCM) under two Shared Socioeconomic Pathways (SSP2-4.5 and SSP5-8.5) scenarios from 2021 to 2100. The baseline period (1970–2000) corresponded to a mean soil loss of 29.56 t ha−1 yr−1 and a sediment yield of 6.81 t ha−1 yr−1. Under SSP2-4.5, soil loss exhibited small fluctuations forming a subtle U-shaped pattern, while SSP5-8.5 projected reductions driven by decreased precipitation. While climate projections influenced temporal variations in soil loss magnitudes, the spatial distribution of high-risk zones remained predominantly controlled by the basin’s steep topography. These persistent erosion hotspots highlight the need for targeted conservation strategies, aligning with efforts to mitigate land degradation Sustainable Development Goal 15.3 (SDG 15.3).